The HMA-domain protein Ict1 is required for Ferroptosis in the rice blast fungus - Shen, Qing; Samu Shihabdeen, Madiha Natchi; Harata, Ken; Naqvi, Naweed I. (Frontiers in Plant Science, 2025)
Lipid peroxidation and iron-dependent cell death, Ferroptosis, in conidia plays a crucial role in ensuring proper infection structure formation and function in the rice blast fungus Magnaporthe oryzae. However, the distribution of such important cation(s) in regulating precise developmental cell death remains unexplored. Here, we characterized the role of an iron-copper chaperone (Ict1) and a copper transporter (Ccc2) in growth and pathogenesis in Magnaporthe. These Heavy-Metal-Associated domain containing proteins, particularly Ict1, were found to be important for Ferroptosis in rice blast conidia. Loss of Ict1 or Ccc2 induced significant viability in the three conidial cells in contrast to the sequential demise therein in the wild-type M. oryzae. Furthermore, an increased accumulation of oxidized lipids at the plasma membrane was evident in wild-type, but not in the ict1Δ or ccc2δ conidial cells undergoing pathogenic differentiation. The ict1δ showed a lack of iron accumulation in conidia at the crucial time points, and such defects in cation homeostasis and cell death were suppressed significantly upon exogenous provision of ferric ions, and to a minor extent with copper. Interestingly, the ict1δ conidia exhibited diminished mitophagy and in turn led to a profound increase in mitochondrial membrane potential and stability suggestive of enhanced organellar function that correlates negatively with conidial cell death via Ferroptosis. Lastly, Ict1-GFP was found to be predominantly cytosolic and excluded from the vacuoles during the vegetative and infection-related development in rice blast.